When Queer Studies Meet Intersectional Theory. Conceptual Innovations in Sociological Research on Anti-Lgbtq Violence and Discrimination - Trappolin, Luca (Italian Sociological Review, 2026)
The concepts of homonormativity and homonationalism have been introduced in social research on anti-LGBTQ violence and discrimination since the early 2000s, facilitating significant transformations of the field. Primarily, they have promoted critical examinations of the ambivalent effects produced by mobilisations and politics addressing the so-called homophobia. Empirical research has, in fact, elucidated that the defence of LGBTQ rights may engender the normalisation of white, affluent and gender confirmative non-heterosexual subjects, whilst reinforcing the devaluation of non-Western cultures and queers who experience subordination in axes of social stratification such as race, ethnicity, gender and class. The paper discusses the aforementioned innovations as they represent the most fruitful outcomes of the dialogue between queer studies and intersectionality, which has emerged to overcome their respective limitations. This dialogue has encouraged the formulation of an intersectional model of queer studies and the practice of queering intersectionality, both of which investigate how heteronormative patriarchy, racism and cisnormativity are mutually constitutive of each other in the foundation of social order. The aim of the paper is twofold. Firstly, it synthesises the main elements that have solicited and fostered the reciprocal dialogue between queer studies and intersectional theory. Secondly, it traces the origins of the concepts of homonormativity and homonationalism and provides examples of their application and empirical achievements in social research on anti-LGBTQ violence and discrimination. The conclusive section of the paper illustrates how the investigation of so-called homophobia in Italian research has integrated the transformation of the field.